Neurogenic Arthropathies of the Lower Limbs: About A Case Followed in Rehabilitation at the Chu-Bogodogo - Tiaho, Yirozounlomian; Charles, Sougué; Louis, Tougma; S.I, Traoré; Boukari, Sebgo; B, Bamogo; Salif, Gandema (Surabaya Physical Medicine and Rehabilitation Journal, 2024)
Abstract we report a case of pelvic limb neurogenic arthropathies (NA) in a young 25-year-old patient following severe cranioencephalic trauma in a road traffic accident. The aim of this clinical case was to report the contribution of physical medicine and rehabilitation in the management of neurogenic arthropathies. The patient was admitted to the Physical Medicine and Rehabilitation Department only six months after his trauma. Nervous system disorders were represented by a frontal syndrome and significant spasticity in the pelvic limbs. Deficiencies founds was pain, multiple joint stiffness of the pelvic limbs, induration of the thighs related to arthropathies objectified to the standard x-ray of the thighs. The rehabilitation approach consisted of postures associated with targeted cryotherapy of the muscles. The gait rehabilitation was done gradually between the parallel bars and then with a deanbulator Rehabilitation led to functional improvement, with the patient returning to independent walking using simple techniques. The presentation of this case study provided an overview of this pathology, its functional consequences and the role of Physical and Rehabilitation Medicine in the management of NA. The techniques we used have made it possible to limit the diffusion processes of neurogenic arthropathies by limiting inflammation through associated cryotherapy sessions. The presence of nervous system disorder such as frontal syndrome could have limited rehabilitation, but thanks to collaboration with psychiatrists the evolution was favorable and allowed the patient to actively participate in his rehabilitationThe case also underlined the importance of multidisciplinary patient management, which should be a goal for all practitioners. Keywords: arthropathies ; cryotherapy ; neurogenic ; rehabilitation ; traumatic brain injury